Time management training - Downs, Lisa J. (ASTD trainer's workshop series., 2008)
"Time Management Training reveals how to help others develop strategies for increased productivity and effectiveness. Workshops cover scheduling, delegating, procrastinating, managing distractions, overcommitting, managing email, and completing paperwork. Part of the ASTD trainer's workshop series--ASTD's done all the work for you with complete, customizable, ready-to-use programs. Titles offer half-day, one-day, and two-day workshop formats, as well as all the exercises, handouts, assessments, structured experiences, and presentations needed for effective delivery. PowerPoint slides and electronic copies of all supporting materials for this title are provided online as downloadable content."--Publisher's description.